PENGARUH PROSENTASE KOH TERHADAP PRODUKSI BROWNS GAS DALAM PROSES ELEKTROLISIS DENGAN MENGGUNAKAN ELEKTROLISER DRY CELL - Rachman, Rifqi Mahaputra; Margianto, Margianto; Marlina, Ena (Jurnal Teknik Mesin, 2017)
Alternative energy is being intensively developed to become a new fuel that is hydrogen. To be able to produce hydrogen gas can be done using water electrolysis process by outlining the H2O into HHO gas (Hydrogen Hydrogen Oxygen) using DC current, with HHO Generator media using electrodes such as Stainless Steel plate 304. In this research investigated the efficiency, speed of production, and the power generated by the generator HHO Dry Cell type using KOH catalyst by varying the catalyst is 3,4,5%. Specifications of the generator itself is using Stainless Steel plate 304 with the number of 10 electrodes (plates) is divided into two plate anode (+), 1 plate cathode (-), and 7 plate neutral, with plate thickness of 2mm with the distance between the electrodes of 2mm. results of research and testing HHO generator type of Dry Cell is obtained mixture catalyst is best to use a mixture of 3% KOH in 500ml of distilled water, data showed that the required power generator at 48 watts, with the efficiency of the generator by 64%, while the rate of production of HHO gas for 0.00475 l / s